Ecosystems of Co-Creation - Eckhardt, Jennifer; Kaletka, Christoph; Krüger, Daniel; Maldonado-Mariscal, Karina; Schulz, Ann Christin (Frontiers in Sociology, 2021)
Citizen science is becoming increasingly important as a new and participative mode of knowledge production. An essential element of citizen science is co-creation. Co-creation is by no means limited to a modus operandi for participatory science, but introduces a form of collaborative way of working with society in the sense of citizen science. Results from the H2020 SISCODE project show that co-creation is located inside and between different sectors of society. This article focuses on the question of how co-creation can be better understood in different contexts, and presents a heuristic model that has already been used for case study analyses in the SISCODE project. After an introduction to the field of co-creation and a brief description of the heuristic model, its capability is exemplarily demonstrated via application to two selected cases, followed by a discussion of central learnings and implications for further research on co-creation.